2015
DOI: 10.1016/j.bbapap.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Properties of phosphorylated thymidylate synthase

Abstract: Thymidylate synthase (TS) may undergo phosphorylation endogenously in mammalian cells, and as a recombinant protein expressed in bacterial cells, as indicated by the reaction of purified enzyme protein with Pro-Q® Diamond Phosphoprotein Gel Stain (PGS). With recombinant human, mouse, rat, Trichinella spiralis and Caenorhabditis elegans TSs, expressed in Escherichia coli, the phosphorylated, compared to non-phosphorylated recombinant enzyme forms, showed a decrease in Vmax(app), bound their cognate mRNA (only r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Considering strong influences of posttranslational modifications on kinetics and inhibition of TS-catalyzed reaction [9,26,27] and resulting wide variability of properties of the enzyme preparations of the same specific origin [2,9,27], a simple comparison of mTS and hTS properties would not answer the former question. However, Gibson et al [28] obtained a mutant R163K of the human enzyme and found its catalytic activity to be higher than that of the parental hTS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering strong influences of posttranslational modifications on kinetics and inhibition of TS-catalyzed reaction [9,26,27] and resulting wide variability of properties of the enzyme preparations of the same specific origin [2,9,27], a simple comparison of mTS and hTS properties would not answer the former question. However, Gibson et al [28] obtained a mutant R163K of the human enzyme and found its catalytic activity to be higher than that of the parental hTS.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme preparation was separated into phosphorylated and non-phosphorylated fractions as previously described [12]. Only the non-phosphorylated fraction was used for crystallization.…”
Section: Separation Of Non-phosphorylated Fraction Of Purified Recombmentioning
confidence: 99%
“…ref. 16), only the upper one shows the presence of a phosphate group, as detected in lane 2, causing lower electrophoretic mobility of the phosphorylated subunit). Assuming the presence of a fraction of TS molecules phosphorylated on both subunits, it was too small to be detected.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, rare enzyme molecules that underwent phosphorylation in bacterial cells on both subunits could be lost in the process of MOAC, the loss also remaining undetected. The two TS fractions have been previously characterized by comparing their 31 P NMR spectra and found to contain unmodified and histidine-phosphorylated enzymes, 16 respectively. The latter was evidenced by the phosphorylated fraction spectrum containing a resonance at 2.14 ppm, belonging to inorganic phosphate, and two upfield shifted singlet peaks at À7.39 ppm and À9.87 ppm, with the singlet resonances in the negative spectrum region assigned to reflect N-phosphorylated histidine species (3-pHis and 1-pHis, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation